A Novel Mutation in the MBTPS2 Gene Resulting in Ichthyosis Follicularis, Atrichia, and Photophobia Syndrome - Shin, Jun-Oh; Roh, Dongyoung; Shin, Kihyuk; Kim, Woo-Il; Yang, Min-Young; Lee, Won-Ku; Kim, Hoon-Soo; Kim, Byung-Soo; Kim, Moon-Bum; Ko, Hyun-Chang (Annals of dermatology, 2022)
Ichthyosis follicularis, atrichia, and photophobia (IFAP) syndrome is a rare genetic disorder caused by mutations in the gene. It is characterized by ichthyosis and alopecia from birth. Photophobia may be present in infancy or early childhood. Its mode of inheritance is X-linked recessive; thus, it mostly affects male. The disease severity varies, ranging from mild cases limited to the skin to the severe variant involving multiple extracutaneous features. A 7-year-old boy presented with scanty hair on scalp and eyebrows at birth. On physical examination, scaly patches were observed on the whole body and spiky follicular hyperkeratotic papules were observed on the face and trunk. He also suffered from severe photophobia. Histopathological examination of the scalp showed miniaturized hair follicles without perifollicular fibrosis. Genetic analysis revealed a novel mutation in the gene which was a homozygous missense mutation of c.245T>C leading to an amino-acid substitution from phenylalanine to serine (p.Phe82Ser). We diagnosed this patient with IFAP syndrome. To date, 25 pathogenic gene mutations have been identified. To our knowledge, c.245T>C is a novel homozygous missense mutation in the gene, which has not been reported in Human Gene Mutation Database, ClinVar Database, and Leiden Open Variation Database. Previous reports suggested genotype-phenotype correlations in the gene mutations. Supported by a previous notion that genotype correlates with phenotype, this novel mutation can be a predictive factor for the mild form of IFAP syndrome, restricted to the classic symptom triad.